Anti-herpesvirus prophylaxis, pre-emptive treatment or no treatment in adults undergoing allogeneic transplant for haematological disease: systematic review and meta-analysis. (February 2020) - Beyar-Katz, O.; Bitterman, R.; Zuckerman, T.; Ofran, Y.; Yahav, D.; Paul, M.
Abstract: Background: Herpesviridae infections incur significant morbidity and indirect effects on mortality among allogeneic haematopoietic cell transplant (allo-HCT) recipients. Objectives: To study the effects of antiviral prevention strategies among haemato-oncological individuals undergoing allo-HCT. Data sources: Cochrane Central Register of Controlled Trials, MEDLINE, Embase and LILACS. We further searched for conference proceedings and trial registries. Study eligibility criteria: Randomized controlled trials (RCTs). Participants: Adults with haematological malignancy undergoing allo-HCT. Interventions: Antiviral prophylaxis versus no treatment/placebo or pre-emptive treatment and pre-emptive treatment versus prophylaxis with the same agent. Methods: Random-effects meta-analysis was conducted computing pooled risk ratios (RR) with 95% CI and the inconsistency measure (I 2 ). The certainty of the evidence was appraised by GRADE. Results: We included 22 RCTs. Antiviral prophylaxis reduced all-cause mortality (RR 0.83, 95% CI 0.7–0.99; 15 trials, I 2 = 0%), cytomegalovirus (CMV) disease (RR 0.54, 95% CI 0.34–0.85; n = 15, I 2 = 20%) and herpes simplex virus (HSV) disease (RR 0.29, 95% CI 0.2–0.43; n = 13, I 2 = 18%) compared with no treatment/placebo or pre-emptive treatment, all with high-certainty evidence. Furthermore, antivirals reduced HSV infection, CMV pneumonitis, CMV infection and varicella zoster virus disease. Anti-CMV prophylaxis (+/– pre-emptive treatment) compared with pre-emptive treatment alone reduced non-significantly all-cause mortality (RR 0.78, 95% CI 0.6–1.02; n = 8, I 2 = 0%), CMV disease (RR 0.47, 95% CI 0.23–0.97; n = 9, I 2 = 30%) and HSV disease (RR 0.41, 95% CI 0.24–0.67; n = 4, I 2 = 0%) with high-certainty evidence, as well as CMV and HSV infections. Antiviral prophylaxis did not result in increased adverse event rates overall or more discontinuation due to adverse events. Conclusions: Antiviral prophylaxis directed against herpesviruses is highly effective and safe, reducing mortality, HSV and CMV disease, as well as herpesvirus reactivations among allo-HCT recipients. Anti-CMV prophylaxis is more effective than pre-emptive treatment alone with respect to HSV and CMV disease and infection.